2019
DOI: 10.1111/nhs.12643
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary patterns and sociodemographics: A cross‐sectional study of Australian nursing students

Abstract: Lack of time, financial issues, and stressful clinical and educational environments in nursing studies promote higher intakes of convenience and fast foods loaded with fat and sugar, which are linked to reduced mental and physical health. In this study, we examined the dietary patterns of nursing students and their associated sociodemographic factors to inform the development of future health‐promotion interventions. A total of 548 Bachelor of Nursing students were invited to complete a survey. Associations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…A study of nursing students living in a major Australian city found a majority had low intakes of fruit and vegetables and high alcohol intakes, but most met current guidelines for physical activity (Perry, Gallagher, & Duffield, 2015). A recent study conducted by the authors of this report also found that most nursing students follow an unhealthy diet (high in fast food and junk foods), but most of the nursing students in the study were not meeting physical activity guidelines and had poor sleep quality (Binks, Vincent, Irwin, Williams, & Khalesi, 2020;Williams et al, 2019). These findings are supported by previous international studies that have reported high levels of physical inactivity, smoking, alcohol intake, junk food consumption, caffeine intake, and poor sleep behaviors in nursing students (Al-Kandari, Vidal, & Thomas, 2008;Borle, Parande, Tapare, Kamble, & Bulakh, 2017;Burke & McCarthy, 2011;Deasy et al, 2014;Nassar & Shaheen, 2014;Rodríguez-Gázquez et al, 2016;Urasaki et al, 2009).…”
Section: Introductionmentioning
confidence: 61%
“…A study of nursing students living in a major Australian city found a majority had low intakes of fruit and vegetables and high alcohol intakes, but most met current guidelines for physical activity (Perry, Gallagher, & Duffield, 2015). A recent study conducted by the authors of this report also found that most nursing students follow an unhealthy diet (high in fast food and junk foods), but most of the nursing students in the study were not meeting physical activity guidelines and had poor sleep quality (Binks, Vincent, Irwin, Williams, & Khalesi, 2020;Williams et al, 2019). These findings are supported by previous international studies that have reported high levels of physical inactivity, smoking, alcohol intake, junk food consumption, caffeine intake, and poor sleep behaviors in nursing students (Al-Kandari, Vidal, & Thomas, 2008;Borle, Parande, Tapare, Kamble, & Bulakh, 2017;Burke & McCarthy, 2011;Deasy et al, 2014;Nassar & Shaheen, 2014;Rodríguez-Gázquez et al, 2016;Urasaki et al, 2009).…”
Section: Introductionmentioning
confidence: 61%
“…Using a cross‐sectional study design, bachelor of nursing (BN) students from two universities (one regional and one metropolitan university) in Queensland, Australia, were invited to complete an online survey. A more detailed description of the study methodology has been described elsewhere (Binks et al, 2021; Williams et al, 2020). Briefly, the SurveyMonkey (SurveyMonkey Inc. San Mateo, California, USA, http://www.surveymonkey.com/) platform was used for data collection.…”
Section: Methodsmentioning
confidence: 99%
“…Nutrition behaviors were reported as dietary patterns, food groups (based on classifications outlined in the Australian Dietary Guidelines [National Health and Medical Research Council, 2013]), energy and nutrient intake, and meal frequency (breakfast, morning snack, lunch, afternoon snack, dinner, bedtime snack). The assessment method for dietary patterns has been described in detail elsewhere (Williams et al, 2020). Briefly, dietary patterns were derived using factor analysis with principal component and varimax rotation following cluster analysis of food items.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to behavioral theories and models of individual theories (Opalinski et al, 2018; Short & Mollborn, 2015), the health choices approach emphasizes their agency and their individual opportunities to influence and control their decision‐making (Ivanitskii, 2016; Moilanen, Pietilä, Coffey, Sinikallio, & Kangasniemi, 2018; Paternoster & Pogarsky, 2009). For example, in recent years attention has been paid to adolescents' particular health choices in areas such as dietary patterns (Tebar et al, 2020; Williams et al, 2020), exercise (Matud & Díaz, 2020), and smoking (Ho et al, 2020; Veronda et al, 2020), and their associations with background factors and health. However, little is known about adolescents' perceptions of their health choices and how they make them.…”
Section: Introductionmentioning
confidence: 99%